Scanning Horn Simulation Code for Electron Beam Machine Based on Boris Algorithm - A. H. Shali; S Saminto; S. R. Adabiah; F. Lucyana; T Taufik (Atom Indonesia, 2022)
A numerical particle simulation code package to estimate the irradiation distribution of an electron beam machine is presented. Particle-to-particle interactions are calculated using particle-in-cell method, while the equation of motion is solved using Boris algorithm. The amplitude of oscillating magnetic field distribution from the scanning horn is obtained using CST magnetic field solver. The code was run using Intel’s i7-10700 processor without multithreading. For cases where particle-to-particle interactions are negligible, the simulation requires about 10 000 seconds to finish. The results show that different shapes of signals will result in different irradiation distributions. For a relatively low magnetic oscillation frequency, it is shown that a triangular signal will result in a more evenly distributed irradiation compared to a sinusoidal signal.